FRI0277 Is Mycophenolate Mofetil Effective in the Treatment of Large Vessel Vasculitis?. (9th June 2015) - Smith, R.; Kuet, K.-P.; Akil, M.; Kilding, R.
Abstract : Background: Primary large vessel vasculitides encompass giant cell arteritis and Takayasu's arteritis. The mainstay of treatment is glucocorticoids, with immuno-suppressants such as methotrexate and azathioprine being used as steroid-sparing agents (1). In the Rheumatology Department at the Royal Hallamshire Hospital, Sheffield, UK mycophenolate mofetil (MMF), a reversible inhibitor of inosine monophosphate dehydrogenase necessary for the growth of B and T cells, has been used as an alternative immuno-suppressant. There is limited data supporting its effectiveness in patients with large vessel vasculitis (2), but anecdotal evidence from clinical practice in Sheffield has shown it to be effective. The aim of this retrospective study is to evaluate the effectiveness of MMF in the treatment of patients with large vessel vasculitis in terms of reduction in steroid dose, reduction in inflammation (C-reactive protein) and overall tolerability of the drug. Methods: A retrospective review of 35 patients with large vessel vasculitis (23 large vessel vasculitis, 5 temporal arteritis, 4 Takayasu's arteritis, 2 aortitis and 1 giant cell arteritis) taking MMF between January 2008 and December 2013 was undertaken. The patient list was created by searching electronically saved clinic letters for the keywords large vessel vasculitis, aortitis, Takayasu's, giant cell arteritis, temporal arteritis and mycophenolate mofetil . Reductions in steroid dose and CRP and adverse effects to MMF were assessed. Results: The patients, 29 women and 6 men with a mean age of 64, had been taking MMF in doses of between 1.5g once daily to 1.5g twice daily for between 1 and 10 years. MMF had a steroid sparing effect in 34 patients (97%) and in 6 cases the steroids were discontinued. 28 patients (80%) experienced a reduction in their CRP over the study period, and 21 (60%) had a CRP of less than 5 at the end of December 2013. The mean CRP at initiation of MMF was 24.1 and at the end of the study period it was 7.6. 28 patients continued taking MMF, 25 (71%) at the highest doses prescribed. 13 patients (37%) experienced adverse events whilst taking MMF, but these led to the termination of treatment in only 3 cases (9%). 4 patients (11%) had additional medications added in to the mycophenolate. Conclusions: MMF is an effective and well tolerated treatment for large vessel vasculitis. This retrospective review showed it to have a steroid sparing effect in 97% of patients and to lead to a reduction in CRP in 80%. 37% of patients experienced adverse events but these led to the discontinuation of MMF in only 9%. The results are comparable with those from previous studies demonstrating the effectiveness of MMF in the treatment of large vessel vasculitis, but they augment the evidence by incorporating larger patient numbers over a longer follow-up period. References: Mukhtyar C, Guillevin L, Cid M, et al. EULAR recommendations for the manangement of large vessel vasculitis. Annals of the Rheumatic Diseases 2009:68: 318-323. Kotter I, Henes J, Wagner A, et al. Does glucocorticosteroid-resistant large-vessel vasculitis (giant cell arteritis and Takayasu arteritis) exist and how can remission be achieved? A critical review of the literature. Clinical and Experimental Rheumatology 2012:30(1 Suppl 70): 114-129. Disclosure of Interest: None declared